The Effect of Muscle Fatigue of the Non-Paretic Limb on Postural Control of Stroke Patients - McEwen, Daniel W. D. (Université d'Ottawa / University of Ottawa, 2011)
Since a significantly greater percentage of body weight is supported by the non-paretic limb following stroke, a greater amount of fatigue may be present during daily activities. This may affect the ability of these individuals to maintain a stable upright posture. The presence of falls following a stroke has been attributed in part to this asymmetrical stance post-stroke. Therefore the purpose of this study was to assess the effect of quadriceps muscle fatigue on bi-pedal posture in individuals who had a stroke and an age-matched control group. Although individuals after stroke displayed greater postural sway under the paretic limb than the non-paretic limb or control subjects, results of this study show that sustaining an isometric knee extension of the non-paretic limb induces changes in postural control for individuals after stroke, but that these changes do not markedly differ from those of healthy age-matched controls.
Keywords: Stroke; Posture; Muscle Fatigue